Keragaman pangan dengan kejadian kurang gizi pada anak usia 6-23 bulan - Kamila, Luthfi Nurul; Hidayanti, Lilik; Atmadja, Taufiq Firdaus Al-Ghifari (Nutrition Scientific Journal, 2022)
Dietary diversity plays a role in meeting nutritional needs to prevent undernutrition in children. This study aims to analyze the relationship between food diversity and the incidence of undernutrition in children aged 6-23 months in Sukarame Village, Sukarame District, Tasikmalaya Regency in 2022. This research method is observational with a cross-sectional design. The research subjects were 74 children who were selected based on the proportional random sampling technique. Data analysis used descriptive statistical tests and Fisher’s tests. The results of the univariate analysis found that the incidence of stunting, underweight, and wasting were 10.8%, 8.1%, and 8.1%, respectively. Most of the subjects in this study consumed various foods (55.4%). Statistical analysis showed that dietary diversity was significantly associated with underweight (p=0,03), but there was no association between dietary diversity and stunting (p=0.725) and wasting (p=0.216) in children aged 6-23 months. Adequate portions and amounts of food must accompany the consumption of food diversity to meet nutritional needs.